Comparing health status after major trauma across different levels of trauma care. Issue 3 (March 2023) - Van Ditshuizen, J.C.; De Munter, L.; Verhofstad, M.H.J.; Lansink, K.W.W.; Den Hartog, D.; Van Lieshout, E.M.M.; De Jongh, M.A.C.; ,; ,; van der Veen, A.; Stevens, C.; Vos, D.; et al.
Highlights: Two large Dutch major trauma cohorts of neighbouring inclusive trauma regions were merged. Major trauma patients in level i trauma centres scored below, and level II/III facilities scored similar to health status populations norms. After adjusting, general health status of respondents one to two years after trauma did not differ significantly across levels of trauma care. Fewer limitations in mobility, self-care, and pain and discomfort were reported in level II facilities in adjusted analysis. Trauma populations differ across levels of trauma care, making it an important factor in analysing quality of trauma care in a network. Abstract: Introduction: Mortality due to trauma has reduced the past decades. Trauma network implementations have been an important contributor to this achievement. Besides mortality, patient reported outcome parameters should be included in evaluation of trauma care. While concentrating major trauma care, hospitals are designated with a certain level of trauma care following specific criteria. Objective: Comparing health status of major trauma patients after two years across different levels of trauma care in trauma networks. Methods: Multicentre observational study comprising a secondary longitudinal multilevel analysis on prospective cohorts from two neighbouring trauma regions in the Netherlands. Inclusion criteria: patient aged ≥ 18 with an ISS > 15 surviving their injuries at least one year after trauma. Health status was measured one and two years after trauma by EQ-5D-5 L, added with a sixth health dimension on cognition. Level I trauma centres were considered as reference in uni- and multivariate analysis. Results: Respondents admitted to a level I trauma centre scored less favourable EQ-US and EQ-VAS in both years (0.81–0.81, 71–75) than respondents admitted to a level II (0.88–0.87, 78–85) or level III (0.89–0.88, 75–80) facility. Level II facilities scored significantly higher EQ-US and EQ-VAS in time for univariate analysis (β 0.095, 95% CI 0.038–0.153, p  = 0.001, and β 7.887, 95% CI 3.035–12.740, p  = 0.002), not in multivariate analysis (β 0.052, 95% CI -0.010–0.115, p  = 0.102, and β 3.714, 95% CI -1.893–9.321, p  = 0.193). Fewer limitations in mobility (OR 0.344, 95% CI 0.156–0.760), self-care (OR 0.219, 95% CI 0.077–0.618), and pain and discomfort (OR 0.421, 95% CI 0.214–0.831) remained significant for level II facilities in multivariate analysis, whereas significant differences with level III facilities disappeared. Conclusion: Major trauma patients admitted to level I trauma centres reported a less favourable general health status and more limitations compared to level II and III facilities scoring populations norms one to two years after trauma. Differences on general health status and limitations in specific health domains disappeared in adjusted analysis. Well-coordinated trauma networks offer homogeneous results for all major trauma patients when they are distributed in different centres according to their need of care.